Biological effect of acupuncture on peripheral facial paralysis - Duan, Wenwen; Chen, Dan; Huang, Zubo; Zeng, Yue; Liu, Shanshan; Wang, Chao; Zhou, Hao (Frontiers in Neurology, 2025)
Peripheral facial paralysis is the dominant treatment disease of acupuncture. A large number of studies have proved the effectiveness of acupuncture in the treatment of peripheral facial paralysis. However, the underlying biological effect remains in an exploratory phase. This article will sort out and summarize the existing research mechanisms from the following aspects: inflammatory response, immune regulation, neurotransmitters, immune response, facial microcirculation, oxidative stress, changes in nerve structure and function, specificity of acupoints, acupuncture intervention time, and other potential mechanisms aiming to provide a scientific foundation for the role of acupuncture in the treatment of peripheral facial paralysis. Furthermore, the review discusses future directions for mechanistic research based on existing findings.